Evaluation of Clearance to Stop Requirements in A Seismically Isolated Nuclear Power Plant - Gyeonghee An; Minkyu Kim; Jae-Wook Jung; Gilberto Mosqueda; Joaquin Fabian Marquez (Energies, 2020)
Seismically isolated nuclear power plants (NPPs) can provide substantial benefits towards reducing the failure probability of NPPs, especially for beyond design basis earthquake shaking. One risk posed by seismic isolation is the potential for pounding to a stop or moat wall, with currently little guidance provided by design standards on how to address this concern. In this paper, a structural model of an isolated NPP based on the Advanced Power Reactor 1400 MW is enveloped with moat walls and advanced bearing models. The bearing models account for large strain behavior through failure based on full-scale experiments with lead rubber bearings (LRBs). Using these analytical models and a measured ultimate property diagram from LRB failure tests, the range of clearance to the stop considering the performance criteria for the NPP is investigated. Although the analysis results are dependent on the particular models, ground motions, and criteria employed, this research provides an overview of the seismic response and performance criteria of an isolated NPP considering the clearance to the stop.